Synergized Multimodal Therapy for Safe and Effective Reversal of Cancer Multidrug Resistance Based on Low‐Level Photothermal and Photodynamic Effects. Issue 31 (21st June 2018) - Xu, Luming; Liu, Jia; Xi, Jiangbo; Li, Qilin; Chang, Bingcheng; Duan, Xianming; Wang, Guobin; Wang, Shuai; Wang, Zheng; Wang, Lin
Abstract: Despite the therapeutic usefulness of near‐infrared irradiation (NIR)‐induced potent photothermal effects (PTE) and photodynamic effects (PDE), they inevitably damage normal tissues, often posing threat to life when treating tumors adjacent to key organs or major blood vessels. In this study, the frequently overlooked, "weak" PTE and PDE (no killing capability) are employed to synergize chemotherapy against multidrug resistance (MDR) without impairing normal tissues. An NIR‐responsive nanosystem, gold (Au)‐nanodot‐decorated hollow carbon nanospheres coated with hyaluronic acid, is synthesized as a doxorubicin (DOX) carrier with excellent photothermal and photodynamic properties. Upon low‐level infrared irradiation, the mild heat of weak PTE moderately boosts DOX unloading, meanwhile the weak PDE moderately disturbs the P‐glycoprotein function for retaining intracellular DOX by impairing mitochondrial ATP production. These two "moderate" alterations are quantitatively and functionally sufficient to augment the efficacy of chemotherapy in reversing MDR without damaging neighboring tissue. Thus, this work creates a gold‐dot‐decorated nanocarbon spheres based nanosystem for trimodal therapy, reveals the therapeutic value of the frequently ignored weak PTE/PDE, and demonstrates that synergizing with chemotherapy to overcome drug resistance does not necessarily require potent PTE/PDE. Abstract : With gold‐nanodot‐decorated hollow carbon nanospheres, it is demonstrated that weak photothermal (W‐PTE) and photodynamic effects (W‐PDE) are sufficient to synergize chemotherapy for effective and safe reversal of cancer multidrug resistance. W‐PTE boosts intracellular drug release and W‐PDE promotes drug retention, which collectively contributes to build up an intracellular high drug concentration, leading to acute cytotoxicity that kills drug‐resistant cancer cells.